OUTCOMES OF A HOME-BASED UNSUPERVISED REHABILITATION PROTOCOL FOLLOWING ROTATOR CUFF REPAIR: A COHORT STUDY - Gupta, Ashis Kumar (Student’s Journal of Health Research Africa, 2024)
Background Rotator cuff tears are a general cause of shoulder pain and dysfunction, often requiring surgical repair. Postoperative rehabilitation is crucial for optimal recovery, but traditional supervised physical therapy can be resource-intensive and costly. This study aimed to evaluate the outcomes of a home-based unsupervised rehabilitation protocol following rotator cuff repair performed through a mini-open incision. Methods A cohort study was carried out involving 50 individuals who underwent rotator cuff repair. Patients were taught a standardized home-based rehabilitation protocol and followed up at regular intervals. Pain levels (VAS score), functional status (DASH score), range of motion, cuff strength, and return-to-work rates were assessed over a 12-month period. Statistical analyses were performed to compare pre–operative and postoperative outcomes. Results Significant improvements were observed in pain levels, with the mean VAS score decreasing from 7.8 preoperatively to 2.3 at one year postoperatively (p < 0.001). The DASH score improved from a mean of 65.4 preoperatively to 20.7 postoperatively (p < 0.001). Forward flexion increased from 85.3 degrees to 165.7 degrees, and external rotation improved from 20.4 degrees to 55.6 degrees (both p < 0.001). Cuff strength increased from 48% to 92% of the opposite side (p < 0.001). Ninety percent of patients returned to full work duties within a mean of 10.2 weeks. The failure rate was low at 6%. Conclusion The home-based unsupervised rehabilitation protocol after rotator cuff repair significantly improved pain, functional status, range of motion, and cuff strength. Most patients returned to work promptly, and the low failure rate indicates this approach is effective and safe. Recommendations Home-based unsupervised rehabilitation should be considered a viable option for postoperative recovery following rotator cuff repair, providing a cost-effective and accessible alternative to supervised therapy. Further research with larger sample sizes and long-term follow-up is recommended to validate these findings.